(untitled) (Damu Journal of Sport Sciences, 2024)
The aim of the research was to identify positive thinking, psychological security, self-confidence, and accuracy of handball shooting, as well as to find the relationship between positive thinking, psychological security, and accuracy of handball shooting for the research sample members, that the development of achievement in all sports depends largely on the psychological aspect, and one of the important psychological aspects is positive thinking, which plays a major role in improving the performance of athletes and increasing their chances of success by applying a set of practices and methods that help athletes focus, motivate themselves, and achieve their goals more effectively, as well as psychological security, which expresses the feeling of security and psychological confidence enjoyed by athletes, whether they are players or coaches, and has great importance in the sports field, especially its impact on sports performance, in addition to self-confidence, which has a major role in the performance of athletes and their development in the sports field through the athlete's belief in his ability to achieve his goals and excel in competitions, as it is not just a feeling, but it is The result of training and accumulated experiences, which are necessary to achieve optimal performance in the sports field, as the researcher used the descriptive approach with correlational relationships to suit it to solve the research problem, and the research sample was chosen intentionally from the students of Section (B) of the third stage in the College of Physical Education and Sports Sciences at the University of Anbar with a number of (20) students, and the researcher also used some means, devices and tools that suit the research work, then conducted a survey experiment, and then conducted the main experiment by implementing the tests used in the research, and then unloading the data and processing it statistically, and then displaying, analyzing and discussing it, and then the researcher reached the conclusions that positive thinking has a role in significantly raising the level of psychological security among the members of the research sample, as well as that positive thinking has a role in significantly raising the level of self-confidence among the members of the research sample, as well as that positive thinking has a role in developing the accuracy of handball shooting in a clear positive way among the members of the research sample.